Various Adjuvants Effect on Immunogenicity of Puumala Virus Vaccine - Kurashova, Svetlana S.; Ishmukhametov, Aidar A.; Dzagurova, Tamara K.; Egorova, Maria S.; Balovneva, Maria V.; Nikitin, Nikolai A.; Evtushenko, Ekaterina A.; Karpova, Olga V.; Markina, Anna A.; Aparin, Peter G.; Tkachenko, Petr E.; L`vov, Vyatcheslav L.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Various adjuvant effects on the immunogenicity of the candidate inactivated Puumala virus vaccine were detected in BALB/c mice. Adjuvants under study were: aluminum hydroxide, spherical particles of Tobacco mosaic virus coat protein, B subunit of heat-labile enterotoxin of Escherichia coli, and low endotoxic lipopolysaccharide of Shigella sonnei. Aluminum hydroxide (1 mg/ml) did not affect neutralizing antibodies’ induction and vaccine stability during storage compared to immunization with the vaccine without adjuvant. B subunit of heat-labile enterotoxin (0.2 µg/ml), low endotoxic lipopolysaccharide (50 µg/ml), and plant virus-based spherical particles (300 µg/ml) significantly enhance the humoral immune response of vaccine (p < 0.0001). Pronounced stimulation of IL-12 and IFN-ɣ was observed when mice were immunized with vaccines both with adjuvants (except of aluminum hydroxide) and without adjuvants. It has been shown that low endotoxic lipopolysaccharide contributes not only to enhance the immune response but also to stabilize vaccine immunogenicity during at least 1 year storage.